2019
DOI: 10.1080/22221751.2019.1621668
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence and experimental infection of cynomolgus macaques with pteropine orthoreovirus reveal monkeys as potential hosts for transmission to humans

Abstract: Pteropine orthoreoviruses (PRV) are emerging bat-borne viruses with proven zoonotic transmission. We recently demonstrated human exposure to PRV in Singapore, which together with previous reports from Malaysia and Vietnam suggest that human infection of PRV may occur periodically in the region. This raises the question whether bats are the only sources of human infection. In this study, we screened 517 cynomolgus macaques caught in Singapore for evidence of exposure to PRV3M (also known as Melaka virus), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This provides evidence that S2 and S4 diversity, across the geographic distribution of PRV, is not significantly structured by factors such as host species. In other words, PRV appears to have a broad host tropism [3]. We note that our analyses assume that human PRV infections were acquired locally, or, for imported cases, at the reported site of infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This provides evidence that S2 and S4 diversity, across the geographic distribution of PRV, is not significantly structured by factors such as host species. In other words, PRV appears to have a broad host tropism [3]. We note that our analyses assume that human PRV infections were acquired locally, or, for imported cases, at the reported site of infection.…”
Section: Discussionmentioning
confidence: 97%
“…Although the mechanism by which PRV transmits between bat species across the range of the virus remains incompletely known, these studies suggested that co-roosting behavior is a major driver of such transmission. The transmission of PRV between related bat species should occur with relative ease under permissive ecological conditions, given the aforementioned zoonotic potential of PRV and further evidence of infection of wild crab-eating macaques (Macaca fascicularis) in Singapore [3] and Thailand [45]. We anticipate that future surveys of pteropids bats of south Asia, the Middle East, and the Horn of Africa may further expand the range of PRV and fill the gaps in the geographic continuum of genetic distance that we have documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the performed infection assays, HEK293T cells were employed to investigate the effects of BAG3 overexpression or knockdown on lytic infection of PRV. We used HEK293T cells because: (i) Human cell lines are susceptible to PRV, and support the efficient replication of PRV [35,36], (ii) HEK293T cells are highly efficient for overexpression of foreign protein by the transfected plasmid, and (iii) PRV has been reported in several recent case reports to infect humans, which results in encephalitis [37][38][39][40][41][42]. Both overexpression and knockdown assays indicated that BAG3 played a negative regulation role during PRV lytic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Bats are well recognized as natural hosts of multiple highly pathogenic zoonotic viruses, such as Marburg virus [ 1 ], SARS-CoV [ 2 ], MERS-CoV [ 3 ], Hendra virus [ 4 ], Nipah virus [ 5 ], and Ebola virus [ 6 ]. Viral transmission to humans directly from bats or via other animals as intermediate hosts has occurred previously, causing fatal outbreaks in humans and suggesting an important role of bats in disease transmission [ 1 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%